Effect of DLC films with and without silver nanoparticles deposited on titanium alloy - Ankha, Milagros del Valle El Abras [UNESP]; Silva, Alecsandro de Moura [UNESP]; Do Prado, Renata Falchete [UNESP]; Camalionte, Maiara Penteado [UNESP]; De Vasconcellos, Luana Marotta Reis [UNESP]; Radi, Polyana Alves; Sobrinho, Argemiro Soares Da Silva; Vieira, Lucia; Carvalho, Yasmin Rodarte [UNESP] (FapUNIFESP (SciELO), 2019)
Diamond-like carbon (DLC) film is a biocompatible hard coating material that can prevent the leaching of metal ions. This study evaluates the structural characteristics of DLC, with and without silver nanoparticles, deposited by plasma (PECVD) on titanium alloy (Ti-6Al-4V) and bone formation in contact with DLC films. Sixty Ti-6Al-4V samples were used divided in: Uncoated, coated with DLC and coated with DLC-Ag. After structural characterization, samples were fixed bilaterally at the rabbit's mandible. After 15 and 90 days, samples were characterized again and bone formation in the area was analyzed by histomorphometry. Statistical analysis was performed by two-way ANOVA. Both the DLC and DLC-Ag films were firmly adhered and showed a high electrical resistance without significant changes in the Raman spectrum after in vivo integration. After 15 days, there were immature bone trabeculae in the interface and partially covering the surface. After 90 days, mature bone filled the interface and coved the surface. There was no statistically significant difference among the three groups in both periods. In conclusion, osseointegration with DLC, DLC-Ag and uncoated Ti-6Al-4V is similar. However, DLC and DLC-Ag coverings have the advantage of electrical insulation and can presumably control bacterial activity and ion leaching.
Keywords: Diamond-likecarbon; Osseointegration; Plasma-enhanced chemical vapor deposition